FAULT STABILITY EVALUATION USING ONE DIMENSION GEOMECHANICAL ANALYSIS FOR CCS STUDY AT SKW FIELD, BOJONEGORO DISTRICT, EAST JAVA - Imam Rafii, Fachrizal
The SKW Field is part of North East Java Basin which located in Bojonegoro District, East Java. There are two reservoirs which can be used as CO2 injection target, Ledok Formation and Tuban Formation and both of them have limestone lithology. SKW Field has overpressure zone that affects in situ stress value. This research was conducted with geomechanical analysis approach. This approach uses well log data to find the main stress value that worked in this field, in the form of vertical stress (Sv) from log density processing, pore pressure (Pp) using empirical equation of sonic log, minimum horizontal stress (Shmin) using empirical equation and leak off test data, and maximum horizontal stress (SHmax) generated from empirical equations through borehole breakout data and tensile fracture data. The one dimensional mechanical earth model is generated by integrating all the value. From there, the model is used to analyse the fault stability, from these three paramaters value, slip tendency (Ts), dilation tendency (Td), and fracture stability (Fs). These one dimensional mechanical earth model results show that the dominant stress configuration in SKW Field is SHmax > Sv > Shmin. Image log data shows the maximum horizontal stress direction of SKW Field having northeast-southwest. SKW field has an overpressure phenomenon at the Wonocolo Formation and the Ngrayong Formation. This phenomenon causes decrasing the difference of the value between the maximum horizontal stress and the minimum horizontal stress. Based on the faults slip tendency (Ts) value that located in SKW Field with the east-west direction, the value of slip tendency range between 0-0,37 to the current stress. However, the dilation tendency (Td) value, range between 0,42-0,89 to the current stress. Fracture stability (fs) analysis shows that the fluid pressure can be added to reservoir which connect to the faults in SKW Field has an injection capability of 10,6 MPa-14,3 MPa.